ZnxCu(1-x)Fe2O4 Nanoferrites by Sol-Gel Auto Combustion Route: Cation Distribution and Microwave Absorption Properties - Kavas, H.; Baykal, A.; Demir, A.; Toprak, M. S.; Aktas, B. (Springer, 2014)
The effect of Zn doping on magnetic properties and site preference of cations of CuFe2O4 has been investigated. Zn substituted Cu ferrite nanoparticles with general formula ZnxCu(1-x)Fe2O4 were synthesized by a sol-gel auto combustion method. Samples showed fine particle size with very strong aggregation, due to the high temperatures attained during the combustion process. All samples showed high phase purity assessed from X-ray diffraction analysis and do not have magnetization hysteresis, which reveals superparamagnetic character of the fabricated particles. It was found that a certain amount of Zn substitution in Cu ferrite (0.4 < x < 0.6) causes different site occupation of cations. XRD and magnetic hysteresis data of all samples were analyzed and the cation distribution in spinel ferrites was calculated by these two experimental techniques. It was found that the Neel antiferromagnetic aligned sublattice model is valid below this region (x < 0.4), and above it (x > 0.6) the canted spins at octahedral site are dominant according to the tetrahedral site spins.
Keywords: Magnetic materials; Reflection loss; Cation distribution; Permittivity; Permeability